Detection of Dengue Virus in Department of Bolivar, Colombia, 2012-2013, Real-Time PCR - Gómez Camargo, DORIS ESTHER; García Toscano, Yina Paola; OCHOA, MARGARITA MARIA; Castro, Raimundo; Camacho, Erwin; Tuirán, Pedro Blanco (JOURNAL OF ADVANCES IN BIOTECHNOLOGY, 2014)
Objective. To assess the presence of RNA from dengue virus by Real Time Polymerase Chain Reaction with Reverse Transcriptase (qRT-PCR), in anti-dengue IgM seronegative serum samples obtained from symptomatic patients with less than 5 days of fever, in the department of Bolivar, Colombia. Materials and Methods. Cross sectional descriptive study, where 50 anti-dengue IgM seronegative serum samples were analyzed by qRT-PCR. In addition, we reviewed the epidemiological charts of each patient in order to collect sociodemographic and blood count (CBC) data. Results. DENV-3 RNA was detected in seven (14Â %) serum samples. The most common clinical manifestations were: fever (90Â %; 45/50), headache (88Â %; 44/50) and myalgia (74Â %; 37/50). Regarding the CBC, the most significant findings were: thrombocytopenia (60Â %; 30/50; 73.3% were men), and leukopenia (50Â %; 25/50; 60% were men). Conclusion. Detection and typing of DENV genome by qRT-PCR could be considered a diagnostic tool for Dengue in anti-dengue IgM seronegative serum samples, especially, within four days after the onset of the signs of the disease.